Non–contrast-enhanced magnetic resonance angiography using time-spatial labeling inversion pulse technique for differentiation between pulmonary varix and arteriovenous malformation - Hamamoto, Kohei (Radiol Case Rep, 2017)
Pulmonary varix is a rare entity that presents as a focal aneurysmal dilatation of the pulmonary vein and is frequently mistaken for a pulmonary arteriovenous malformation (PAVM). It is important to distinguish between pulmonary varix and PAVM because the former does not usually require treatment. We present the findings of non–contrast-enhanced magnetic resonance angiography with the time-spatial labeling inversion pulse technique in case of pulmonary varix and PAVM and the utility of this method for differentiating between these diseases.